2019
DOI: 10.1038/s41467-019-12138-0
|View full text |Cite
|
Sign up to set email alerts
|

Synchronous 500-year oscillations of monsoon climate and human activity in Northeast Asia

Abstract: Prehistoric human activities were likely influenced by cyclic monsoon climate changes in East Asia. Here we report a decadal-resolution Holocene pollen record from an annually-laminated Maar Lake in Northeast China, a proxy of monsoon climate, together with a compilation of 627 radiocarbon dates from archeological sites in Northeast China which is a proxy of human activity. The results reveal synchronous ~500-year quasi-periodic changes over the last 8000 years. The warm-humid/cold-dry phases of monsoon cycles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
87
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(89 citation statements)
references
References 48 publications
2
87
0
Order By: Relevance
“…Over the last decade, the use of spectrum analysis on proxy-based paleoclimate reconstructions has produced increasing evidence to confirm the existence of Holocene centennial- to millennial climate cycles (e.g. Obrochta et al, 2012; Ojala et al, 2015; Soon et al, 2014; Stebich et al, 2015; Swindles et al, 2012; Xu et al, 2014, 2019, 2020). However, until now, an agreed theory for these Holocene periodic oscillations and their potential forcing is still lacking.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the last decade, the use of spectrum analysis on proxy-based paleoclimate reconstructions has produced increasing evidence to confirm the existence of Holocene centennial- to millennial climate cycles (e.g. Obrochta et al, 2012; Ojala et al, 2015; Soon et al, 2014; Stebich et al, 2015; Swindles et al, 2012; Xu et al, 2014, 2019, 2020). However, until now, an agreed theory for these Holocene periodic oscillations and their potential forcing is still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Although evidence for millennial- and centennial-scale climate cycles across East Asia is increasing, one single, agreed theory explaining the forcing factor and possible mechanism has not yet emerged (e.g. Beck et al, 2018; Jo et al, 2017; Lu et al, 2019; Stebich et al, 2015; Stevens et al, 2018; Wang et al, 2001, 2005a, 2005b, 2017; Xu et al, 2014, 2019, 2020). Therefore, additional terrestrial records from the EAM region are still required to establish a credible hypothesis regarding the cyclic characteristics of EASM activity.…”
Section: Introductionmentioning
confidence: 99%
“…In South America, Chen et al (2011) identified a correlation between the Oceanic Niño Index and the interannual fire activity in the eastern Amazon, whereas the Atlantic Multidecadal Oscillation index was more closely linked to the occurrence of forest fires in the south and southwest Amazon. A decadal‐resolution Holocene pollen record from northeast China revealed synchronous ~500‐year quasi‐periodic changes of the EASM over the last 8,000 years, which was linked to ENSO (Xu et al, 2019). Along Track Scanning Radiometer data from July 1996 to December 2001 in Indonesia inferred a strong correlation between forest fires and the Southern Oscillation Index ( r = −0.75) and the Niño 3.4 index ( r = 0.72) in forested regions of the equatorial belt (5.5°S–5.5°N) (Fuller & Murphy, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In pollen zone I, Pinus pollen fluctuated but with slight increase trend (Figure 4). Numeric analyses also suggest that the pollen spectra in this zone was impacted by the sPDC which is a proxy of human activity (Wang et al., 2014; Xu et al., 2019). Therefore, the human activity had been impacting the vegetation composition during the pollen zone I.…”
Section: Discussionmentioning
confidence: 95%